Prospective longitudinal study of corneal collagen cross‐linking in progressive keratoconus. (14th December 2012) - Viswanathan, Deepa; Males, John
Abstract Background Collagen cross‐linking has been reported to be effective in treating progressive keratoconus, and this study aims to evaluate the long‐term efficacy of this procedure. Design Prospective longitudinal interventional study of patients with progressive keratoconus who underwent cross‐linking in a tertiary referral hospital. Participants Thirty‐five patients (51 eyes) who underwent cross‐linking with a mean follow‐up of 14.38 ± 9.36 months (range 6–48) were compared with a control group of 25 fellow eyes that did not undergo the procedure. Methods Cross‐linking was performed using 0.1% riboflavin (in 20% dextran T500) and ultraviolet A irradiation (370 nm, 3 mW/cm2, 30 min). Main Outcome Measures Maximum keratometry in dioptres, logMAR best spectacle‐corrected visual acuity, cylindrical power, manifest refraction spherical equivalent and central corneal thickness. Results Analysis of the treated group demonstrated a significant flattening of maximum keratometry by 0.96 ± 2.33 dioptres (P = 0.005) and a significant improvement in visual acuity by 0.05 ± 0.13 logMAR (P = 0.04). In the control group, maximum keratometry increased significantly by 0.43 ± 0.85 dioptres (P = 0.05), and visual acuity decreased by mean 0.05 ± 0.14 (P = 0.2). No statistical differences were noted regarding cylindrical power, spherical equivalent or corneal thickness in both groups. Conclusions Results indicate that corneal collagen cross‐linking using riboflavin and ultraviolet A is effective as a therapeutic option in cases of progressive keratoconus by reducing the corneal curvature and by improving the visual acuity in these patients.